Anxiety and Depression in Patients With Physical Diseases and Associated Factors: A Large-Scale Field Survey in General Hospitals in China - Yang, Wanlin; Xiao, Ling; Yuan, Zhiyong; Huang, Huan; Xiang, Yilei; Liu, Zhongchun; Nan, Cai; Wang, Huiling; Wang, Gaohua (Frontiers in Psychiatry, 2021)
Introduction: To investigate the characteristic of anxiety and depression among patients in general hospitals, and explore the degree of the clinical symptoms and correlated social economic factors. Methods: This is a cross-sectional survey of anxiety and depression in patients with physical diseases, who were suspected of depression and anxiety based on their clinical performance by their physicians and PHQ≧8, from various clinical departments of 57 general hospitals in China. Data regarding demographic characteristics and clinical characteristics were collected. Social and psychological factors and the severity of anxiety or depression were collected through self-rating scales. Finally, we used multivariate logistic regression to identify the factors associated with anxiety and depression in patients with physical diseases. Results: A total of 2105 (84.6%) valid and completed questionnaires were returned. The proportion of anxiety, depression, combined depression and anxiety, either anxiety or depression among the patients with physical diseases from all clinical departments was 63.3%, 75.1%, 57.1% and 81.2% respectively. Further regression analysis indicated that gender, monthly income, specific physical diseases, personality traits, social supports and life negative events were related factors of both anxiety and depression. Conclusions: Anxiety and depression were common in patients with physical diseases, with a high proportion of co-morbidity of anxiety and depression. Females, patients with cancer, poor social support and negative life events reported more severe anxiety and depression. The results may help to understand the present situation of anxiety and depression in general hospitals in china, and identify the patients with high risk of depression and anxiety.